2017
DOI: 10.1161/circulationaha.116.022281
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Insulin-Mediated β 2 -Adrenergic Receptor Activation Prevents Diabetes-Associated Cardiac Dysfunction

Abstract: Background Type-2 diabetes and obesity independently increases the risk of heart failure via incompletely understood mechanisms. We propose that hyperinsulinemia might promote adverse consequences in hearts of subjects with type-2 diabetes and obesity. Methods High fat diet feeding was used to induce obesity and diabetes in wild type mice or mice lacking β2-adrenergic receptor (β2AR) or β-arrestin2. Wild type mice fed with high fat diet were treated with β-blocker carvedilol or G-protein receptor kinase 2 (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
114
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 52 publications
14
114
1
2
Order By: Relevance
“…In contrast, long-term treatment with βAR agonist induced down-regulation of PDE3B and up-regulation of PDE4D [120]. In line with the observation in adipocytes, our recent study shows that in rodent hearts, hyperinsulinemia induces upregulation of PDE4D protein expression and activity, which correlates with cardiac dysfunction [121] (Figure 2). …”
Section: Insulin Activates βAr Downstream Effectorssupporting
confidence: 66%
“…In contrast, long-term treatment with βAR agonist induced down-regulation of PDE3B and up-regulation of PDE4D [120]. In line with the observation in adipocytes, our recent study shows that in rodent hearts, hyperinsulinemia induces upregulation of PDE4D protein expression and activity, which correlates with cardiac dysfunction [121] (Figure 2). …”
Section: Insulin Activates βAr Downstream Effectorssupporting
confidence: 66%
“…However, the Food and Drug Administration-approved SSRI paroxetine was identified using a high throughput aptamer displacement assay to bind directly to GRK2 to inhibit its ability to phosphorylate rhodopsin, tubulin and thyrotropin-releasing hormone receptor, while increasing βAR-stimulated cardiomyocyte (in vitro) and cardiac (in vivo) contractility 7 . Subsequently, paroxetine has been shown to reverse cardiac dysfunction induced by either ischemia 8 or high fat diet 18 , inhibit T cell activation 19 and decrease fibroblast cytokine production 20 . Despite the increasing use of paroxetine in studies in which its effects are attributed to inhibition of receptor desensitization processes classically engaged by GRK2, such as βarr recruitment and GPCR internalization, no studies have confirmed whether it actually attenuates these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed a critical crosstalk between insulin and β-adrenergic signalling, which impairs cardiac contractility in T2D [78, 209]. βAR signalling is increased in heart failure.…”
Section: Mechanisms Contributing To Myocardial Dysfunction In Diabetimentioning
confidence: 99%